Psychological Well-Being Pada Anak-Anak Remaja Panti Asuhan Taslimiyah Krebet Psychological Well-Being In Teenage Children Taslimiyah Krebet Orphanage - Samsul Hidayat; Yusuf Ratu Agung; Rika Fuaturosida (UIN Maulana Malik Ibrahim Malang, 2021)
The research conducted was Psychological Well-Being on the orphanage children who live in the Taslimiyah Krebet Orphanage. From the narrative of the caregivers, there are some children who are not enthusiastic about participating in dormitory activities, still unaware of their potential, less social, and lacked confidence. Psychological Well-Being is a positive attitude for themselves and others, and has a good social relationship with their environment. This research was conducted at the Taslimiyah Krebet Orphanage, by selecting 4 subjects of orphanage teenagers living in the orphanage. The method in this study uses a qualitative method with a case study approach. The techniques used in data collection are through interviews and observations. The result obtained from this study indicates that the orphanage children at the Taslimiyah Krebet orphanage have high psychological well-being. It is proven that they are able to have a good accepting attitude, positive relationships, realize goals in life, have independence, can control the environment, have self-confidence, and understand their potential. It is also reinforced by the existence of good social support factors, the existence of a good economic status, the existence of a strong religion, and the existence of good personality control.